2012
DOI: 10.1016/j.abb.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential domain structure stability of the severe acute respiratory syndrome coronavirus papain-like protease

Abstract: Papain-like protease (PLpro) from severe acute respiratory syndrome (SARS) coronavirus is one of the two proteases involved in the proteolytic processing of the virion polyproteins. In addition, PLpro shows significant in vitro deubiquitinating and de-ISGylating activities. All these findings demonstrated the multifunctional nature of the PLpro. Here we report the sensitivity of PLpro to denaturant urea. An increase in urea concentration induced a reversible biphasic unfolding of the enzyme. Differently, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
5
16
0
1
Order By: Relevance
“…Not surprisingly, the melting temperature of both PL pro s decreased 10-15°C in the presence of disulfiram. These results conform to our earlier finding that the release of zinc ion can destabilize PL pro (Chou et al, 2012). 7)).…”
Section: Disulfiram May Also Act As a Zinc Ejectorsupporting
confidence: 93%
See 2 more Smart Citations
“…Not surprisingly, the melting temperature of both PL pro s decreased 10-15°C in the presence of disulfiram. These results conform to our earlier finding that the release of zinc ion can destabilize PL pro (Chou et al, 2012). 7)).…”
Section: Disulfiram May Also Act As a Zinc Ejectorsupporting
confidence: 93%
“…5A, left panel). Previous studies have suggested that the release of zinc ion following treatment with EDTA will lead to a 62% loss of PL pro activity (Chou et al, 2012). This result is consistent with the effect of disulfiram on PL pro s. Also, the inability of the reductant to rescue the DUB activity of MERS-CoV PL pro , suggesting that disulfiram cannot influence its active site, is compatible with disulfiram's noncompetitive mode of inhibition of the enzyme.…”
Section: Time-dependent Inhibition Of Sars-cov Pl Pro By Disulfiramsupporting
confidence: 83%
See 1 more Smart Citation
“…The protein induction and purification procedures for SARS-CoV, the E168R mutant of SARS-CoV PL pro and MERS-CoV PL pro have been described previously (Chou et al, 2012Lin et al, 2014). The expression plasmid for MERS-CoV PL pro (GenBank accession number NC_019843.2; polyprotein residues 1484-1800) includes 6Â His tag at the C-terminus (Lin et al, 2014).…”
Section: Expression and Purification Of Mers-cov And Sars-cov Pl Promentioning
confidence: 99%
“…S1) and homology modeling, PEDV PL2 pro may be composed of four domains: ubiquitin-like (Ubl), palm, thumb and fingers domains. The latter three domains form a catalytic core and may retain catalytic activity, like that of SARS-and MERS-CoV PL pro s (Chou et al, 2012;Clasman et al, 2017;Lei et al, 2014). In the present study, we made a recombinant catalytic core PEDV PL2 pro and demonstrated its secondary, tertiary and quaternary structural characteristics.…”
Section: Introductionmentioning
confidence: 71%